Case Report: Three cases of drug-coated balloon-only strategy for coronary artery lesions with aneurysms in the chronic phase - Sugawara, Yu (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCoronary aneurysms are rare; therefore, treatment strategies for coronary lesions with aneurysms remain elusive. We describe three cases of coronary artery lesions with aneurysms in patients treated with drug-coated balloons (DCBs).Case descriptionCase 1 had ST-segment elevation myocardial infarction with a right coronary artery aneurysm treated with a paclitaxel DCB. Case 2 had stenoses of the left anterior descending artery and diagonal branch, along with a coronary aneurysm treated using paclitaxel DCBs. Case 3 had a calcified left anterior descending artery with an aneurysm treated using a paclitaxel DCB. The acute outcomes of these cases were favorable, and prognoses based on follow-up computed tomography angiography findings in the chronic phase were also favorable.ConclusionDCBs may be one option for treating coronary artery stenosis or occlusion.